Diseño de un algoritmo genético para un sistema logístico de distribución - Méndez Giraldo, Germán Andrés (Ingeniería, 1999)
For manufacturing business is interesting to improve the customer's service function, this is a function that depends on many variables which the more important are: quality, price and lead time. For this reason in the manufacturing organizations are incorporated the Business Logistic that composed for supply, manufacturing and distribution logistic, the last is occupied of merchandise transshipment to customer and clients. The Logistic is based on experience, mathematical models and other classic techniques, but for the real manufacturing systems, these tools are inadequate and give poor solutions, for that, today analysts offer novelty applications such as Genetic Algorithms. In this article is presented a design of Genetic Algorithm to solve the distribution problem that consist on finding the paths and vehicles to transshipment the products to remotes points. In addition, it is compared with the most conventional tool used for this propone, and demonstrated the cost reduce in a 30%.